Temperature Effects on Radial Propagation of Water Potential in Cotton Stem Bark - Klepper, Betty (1973)
Low temperature affects the lateral movement of water across the xylem-phloem boundary in intact cotton stems. There is a reduction in the effective diffusion coefficient relating free energy flux to water potential gradients with an associated increase in resistance to water flow. Detached phloem and excised leaves do not show this effect of low temperature. Experiments on stem section halves indicate that the effect is probably associated with the cambial region.